Design and analysis solar car chassis - Idham Ariff, Mat Ali (2010)
A solar car is a specialized type of car designed for race and powered by sun energy (solar). This is obtained from solar panels on the surface of the vehicle. Photovoltaic (PV) cells convert the sun's energy directly into electric energy. Solar vehicles are not sold as practical day-to-day transportation devices at present, but are primarily demonstration vehicles and engineering exercises. It have limited seating (usually one, sometimes two people), it have very little cargo capacity, and only be driven during the day. Chassis is one of the important parts and every car passenger has it. This structure was the biggest component in the car and car shape dependent on it. It has a considerable affected to the performance of the car. The primary challenge in developing an effective solar car chassis is to maximize the strength but minimize the weight. There are various types of chassis, each with its own advantages and disadvantages. Every extra pound requires more energy to move down the road. This means that chassis must strive to minimize weight and a key area is the chassis. However, safety is a primary concern and the chassis must meet stringent strength and safety requirements. As the conclusion, this project had achieves its entire objective successfully. This project was done around twelve week included almost all steps of the report such as literature review, design, analysis process and others.